An exploratory study of attractors and detractors in Black graduates' choice of an academic career in a South African higher education institution - Oghenetega, Timothy Oghenefega (Organisational Psychology, 2017)
This study explored the factors that most determine black graduates' career choice and aimed to better understand how these factors impact the career choice/decision to specifically pursue a career in academia in South Africa, bearing in mind that factors that attract and retain are not the same. Based on a total sample of 204 students from a South African university, the research findings indicate that there is a significant relationship between the influence of a role model and black graduates' intention to apply for an academic job. Implications for theory and practice are also discussed.